2020
DOI: 10.1001/jamanetworkopen.2020.15648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Telehealth Treatment by Lay Counselors vs by Clinicians on Depressive Symptoms Among Older Adults Who Are Homebound

Abstract: Key Points Question Is tele-delivered behavioral activation (tele-BA) treatment by bachelor’s-level lay counselors for older adults who are depressed and homebound with low income clinically effective? Findings In this randomized clinical trial with 277 participants, tele-BA by lay counselors and tele-delivered problem-solving therapy by licensed clinicians were significantly more effective than telephone support calls in improving depressive symptoms, disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 40 publications
2
49
0
Order By: Relevance
“…Furthermore, other work has shown that the skills incorporated into MHP intervention, specifically mindfulness skills, are found to reduce loneliness among the younger adults ( 14 ). Additionally, brief behavioral interventions, such as behavioral activation, are shown to decrease loneliness among the home-bound older adults with depression ( 15 , 16 ). Taken together, it is expected that the MHP would both increase mental health quality of life (QoL) and decrease loneliness through increasing acceptance, improving self-regard/self-compassion, reducing negative cognitions, and promoting engagement in the present moment through informal mindfulness practices ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other work has shown that the skills incorporated into MHP intervention, specifically mindfulness skills, are found to reduce loneliness among the younger adults ( 14 ). Additionally, brief behavioral interventions, such as behavioral activation, are shown to decrease loneliness among the home-bound older adults with depression ( 15 , 16 ). Taken together, it is expected that the MHP would both increase mental health quality of life (QoL) and decrease loneliness through increasing acceptance, improving self-regard/self-compassion, reducing negative cognitions, and promoting engagement in the present moment through informal mindfulness practices ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pre‐COVID research on video therapy tends to focus on populations for whom attending in‐person therapy is challenging, such as older home‐bound adults (Choi et al., 2020), people with social anxiety (Yuen et al, 2013), cancer survivors (Lleras de Frutos et al., 2020) and postpartum women (Yang et al., 2019). Research has also focused on the effects of video therapy for rural and remote geographical regions (Saurman et al., 2011; Scogin et al., 2018) and where intersectional needs make finding an appropriately qualified therapist challenging (e.g.…”
Section: Is Video Therapy Effective?mentioning
confidence: 99%
“…20,21,45 Similarly, a randomized controlled trial for tele-based psychotherapy showed that older adults with depression showed significant improvement in their depressive symptoms. 46,47 Consulting Elderly with Family Member/Patient via Telemedicine (Adopted from Telepsychiatry Practice Guidelines 2020)…”
Section: Prescribing Treatment and Comprehensive Managementmentioning
confidence: 99%
“… 20 , 21 , 45 Similarly, a randomized controlled trial for tele-based psychotherapy showed that older adults with depression showed significant improvement in their depressive symptoms. 46 , 47 A qualitative study with caregivers of persons with dementia reported that video and telephonic-based consultations are extremely helpful for caregivers in understanding and playing an active role in managing behavioral problems of their affected older adults. 48 Another study with 433 older adults with symptoms of anxiety and depression has shown that internet-based cognitive behavioral therapy effectively reduced the symptoms when delivered in either clinician-guided or self-guided format.…”
Section: Capacity Assessmentmentioning
confidence: 99%